Answers

2015-02-04T22:48:44+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let the common root be m. Put in the equations;
m² + 4am + 3 = 0   --------------(1)
2m² + 3am - 9 = 0   --------------(2)
multiply equation (1) by 2
2m² + 8am + 6 = 0   -------------(3)
(note that equation 1 and 3 are the same)

subtract (2) from (3); you will get
(2m² + 8am + 6) - (2m² + 3am - 9) = 0
⇒ 5am + 15 = 0
⇒ 5am = -15
⇒ m = - \frac{15}{5a} =- \frac{3}{a}

from equation (1),

 (- \frac{3}{a})^{2} + 4a(- \frac{3}{a})+3=0\\ \\ \frac{9}{a^2} - 12+3=0\\ \\ \frac{9}{a^2} -9=0\\ \\\frac{9}{a^2}=9\\ \\a^2= \frac{9}{9}=1\\ \\a=+1\ or\ -1

So values of a are +1 and -1.


1 5 1
thank you . Your answer is very very good and correct.
thank u for your answer.